Case Report: Management of Traumatic Carotid-Cavernous Fistulas in the Acute Setting of Penetrating Brain Injury - Loggini, Andrea; Kass-Hout, Tareq; Awad, Issam A.; El Ammar, Faten; Kramer, Christopher L.; Goldenberg, Fernando D.; Lazaridis, Christos; Mansour, Ali (Frontiers in Neurology, 2022)
Traumatic carotid-cavernous fistulas (tCCF) after penetrating brain injury (PBI) has been uncommonly described in the literature with little guidance on optimal treatment. In this case series, we present two patients with PBI secondary to gunshot wounds to the head, who acutely developed tCCFs, and review the work-up to diagnosis in addition to treatment of this condition. We highlight the importance of early cerebrovascular imaging as the clinical manifestations may be limited by poor neurological status and possibly concomitant injury. Definitive treatment should be attempted as soon as possible with embolization of the fistula, flow diversion via stenting of the fistula site and finally vessel sacrifice as possible therapeutic options.